XVI International Tchaikovsky Competition: Winner's Gala (I/II) #TCH16 - Tchaikovsky, Peter Ilich 1840-1893; Bach, Carl Philipp Emanuel 1714-1788; Glière, Reinhold Morit͡sevich 1875-1956; Carter, Elliott 1908-2012; Tchaikovsky, Peter Ilich 1840-1893; Tchaikovsky, Peter Ilich 1840-1893; Wagner, Richard 1813-1883; Paganini, Nicolò 1782-1840; Rossini, Gioacchino 1792-1868; Mozart, Wolfgang Amadeus 1756-1791; Mozart, Wolfgang Amadeus 1756-1791; Haydn, Joseph 1732-1809; et al. (MUSEEC, 2019)
The 16th edition of the prestigious International Tchaikovsky Competition comes to an end! After more than a week of intense musical challenges, the new stars of classical music come together to celebrate their triumph! A not-to-be-missed event webcast live on medici.tv and on The Studio. Official partner for the second consecutive edition, medici.tv launched its first continuous channel with 8 hours of non-stop video content webcast live each day, including interviews, rare glimpses backstage, archival footage, and much more ... The main website medici.tv is also co-webcasting the opening concerts, the finale, the awards ceremony and the past winners concerts. A new challenge met with aplomb! This ceremony will mark a decisive moment in the careers of these young stars, whether they win the first prize or not! The pianist who won the first prize in 1958, Van Cliburn, was met with a ticker tape parade on his arrival in New York returning from Russia. Lucas Debargue was met with a tidal wave of fame despite having been in fourth place in the 2015 competition. Cellist Natalia Gutman, violinist Gidon Kremer, singers Hibla Gerzmava and Ariunbaatar Ganbaatar ... all of they passed through the Tchaikovsky Competition on their way to fame. And who are these new stars?
Keywords: Violin music; Tuba with string orchestra, Arranged; Operas; Concertos; Ballets; Ballets -- Excerpts; Concertos -- Excerpts; Operas -- Excerpts, Arranged; Operas -- Excerpts; concert; Songs; Filmed performances; Excerpts; Dramatic music; Dance music; Internet videos